2020
DOI: 10.3390/nu12102975
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease: Are Symptoms and Diet Linked?

Abstract: New Zealand (NZ) has one of the world’s highest incidence rates of Inflammatory Bowel Disease (IBD), a group of chronic inflammatory conditions that affect the gastrointestinal tract. Patients with IBD often believe certain foods influence their disease symptoms and consequently may alter their diet considerably. The objective of this study was to determine foods, additives, and cooking methods (dietary elements) that NZ IBD patients identify in the onset, exacerbation, or reduction of their symptoms. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 78 publications
2
31
1
Order By: Relevance
“…In this study, both UC and CD patients reported avoidance of similar foods due to anticipated aggravation of IBD symptoms (Figure 2). It is noteworthy that the majority of products reported in our study to be detrimental, were also indicated in other studies (De Vries et al, 2019;Morton et al, 2020;Vagianos et al, 2016;Vidarsdottir et al, 2016) which have found processed foods, different fruits and vegetables and various beverages including alcohol, and fruit juices to be detrimental. However, the assessment of the effects of tea and coffee consumption appears to vary across studies.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In this study, both UC and CD patients reported avoidance of similar foods due to anticipated aggravation of IBD symptoms (Figure 2). It is noteworthy that the majority of products reported in our study to be detrimental, were also indicated in other studies (De Vries et al, 2019;Morton et al, 2020;Vagianos et al, 2016;Vidarsdottir et al, 2016) which have found processed foods, different fruits and vegetables and various beverages including alcohol, and fruit juices to be detrimental. However, the assessment of the effects of tea and coffee consumption appears to vary across studies.…”
Section: Discussionsupporting
confidence: 85%
“…However, the assessment of the effects of tea and coffee consumption appears to vary across studies. The intake of these two drinks was previously associated with a higher risk of exacerbation, the recurrence of symptoms and overall avoidance, especially in active disease (Cohen et al, 2014;De Vries et al, 2019;Morton et al, 2020), although in our study, both drinks were found among the most frequently consumed products. Another study on 294 patients with IBD also found that tea was regarded as the second most symptom improving food, thus the effects of tea and coffee on GI symptoms require further research (De Vries et al, 2019).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…According to a study based on a self-administered questionnaire completed by IBD patients, fruit, vegetables and bread with gluten resulted in the exacerbation of symptoms [190]. The meta-analysis showed that a higher intake of vegetables and fruits was negatively associated with UC risk.…”
Section: Low Intake Of Fibre Whole Grain Vegetables and Fruitsmentioning
confidence: 99%
“…A large survey of 233 IBD patients reported that symptom onset and exacerbation were associated with dietary elements in 55% and 70% of patients, respectively [ 70 ]. Besides fruits and vegetables, frequently named ‘deleterious’ foods were dairy products, gluten-containing bread, and foods with a high fat content [ 70 ].…”
Section: Overview Of Different Dietary Strategiesmentioning
confidence: 99%